2000
DOI: 10.1348/135532500167958
|View full text |Cite
|
Sign up to set email alerts
|

Offender profiling and criminal differentiation

Abstract: Purpose. The psychological hypotheses that form the foundations for 'Offender Profiling' are identified and the research that has tested them is reviewed.Argument. 'Offender profiling' is taken to be the derivation of inferences about a criminal from aspects of the crime(s) s/he has committed. For this process to move beyond deduction based on personal opinion and anecdote to an empirically based science a number of aspects of criminal activity need to be distinguished and examined. The notion of a hierarchy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
194
1
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(218 citation statements)
references
References 20 publications
11
194
1
12
Order By: Relevance
“…However, not much is known when it comes to person-oriented offenses such as sex crimes. Here again, still, prior research shows that, while the environmental decision and selection of the site might be influenced by dynamic factors, serial offenders often use the same geographic and ecological space and tend to pattern themselves geographically (e.g., Beauregard, Proulx, Rossmo, Leclerc, & Allaire, 2007;Canter, 2000;LeBeau, 1987). In a recent study, Lundrigan, Czarnomski, and Wilson (2010) examined the consistency displayed by serial sex offenders in regards to the crime location and characteristics of the crime site selected -what they refer to as environmental consistency.…”
Section: Environmental Consistency and Serial Offendersmentioning
confidence: 99%
“…However, not much is known when it comes to person-oriented offenses such as sex crimes. Here again, still, prior research shows that, while the environmental decision and selection of the site might be influenced by dynamic factors, serial offenders often use the same geographic and ecological space and tend to pattern themselves geographically (e.g., Beauregard, Proulx, Rossmo, Leclerc, & Allaire, 2007;Canter, 2000;LeBeau, 1987). In a recent study, Lundrigan, Czarnomski, and Wilson (2010) examined the consistency displayed by serial sex offenders in regards to the crime location and characteristics of the crime site selected -what they refer to as environmental consistency.…”
Section: Environmental Consistency and Serial Offendersmentioning
confidence: 99%
“…As mentioned, a considerable amount of research (reviewed by Canter, 2000) has found non-metric multi-dimensional scaling (MDS) to be useful for finding the underlining themes. SSA is one of the MDS methods that represents the relationship between variables as distances in a geometric space.…”
Section: Smallest Space Analysis (Ssa) and Data Descriptions For The mentioning
confidence: 99%
“…Clarke and Cornish (1985) point out that it will usually be necessary to make finer distinctions between crimes than those provided by legal categories, pointing out that residential burglaries are different from commercial burglaries, although are legally just 'burglaries'. Canter (2000) demonstrates the effectiveness of a thematic approach to the study of criminals' actions. He points to the need to identify the dominant 'themes' amongst variables that characterise an offence rather than focussing on very detailed consideration of specific actions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies [3,4], features have been identified by means of content analysis of the text. Typically, a researcher reads all the documents and identify a set of features.…”
Section: Content Analysismentioning
confidence: 99%